Influence of Fe2O3 nanoparticles on the birefringence property of weakly polar nematic liquid crystal. (11th February 2019) - Yadav, Geeta; Roy, Aradhana; Agrahari, Kaushlendra; Katiyar, Rohit; Chandel, V.S.; Manohar, Rajiv
Abstract: The present paper is invested in studying the measurement of birefringence as a function of the temperature for weakly polar nematic liquid crystals (NLC) doped with magnetic nanoparticles (NPs). A continuous decrease in the value of birefringence is observed on increasing the concentration of NPs. Birefringence is approaching to zero near clearing temperature which is attributed to the deterioration of order parameter in the isotropic phase. The continuous decrease in birefringence with concentration of external dopants has been explained with the help of the perturbation created in the local environment of the molecules due to presence of nanoparticles. Interaction between NPs and NLC molecule reduces the orientation order which causes the decrease in phase retardation and hence reduces the birefringence. The optical micrographs reveal the aggregation in the composite system which is also responsible for decrease of birefringence.